Planners’ ideals and realities : Normative behaviour and conformorality - Qingyuan Guo (Transactions of the Association of European Schools of Planning)
People often make presumptions about planners – rational, altruistic, self-interested, bureaucratic, and so on. However, what is a realist portrait of planning practitioners? What normative dispositions do they tend to adopt, why do they adopt them, and how they behave based on them? To shed light on these questions, this study explores the normative behaviour of planning practitioners. A meta-ethnography was conducted focusing on 19 empirical studies relevant to the normative behaviour of English local authority planners from 1978 to 2022. The paper’s synthesis of the same revealed prominent normative frameworks within the planning community across different social-temporal contexts. The findings highlight consistent normative features among planners: a deep internalisation of a moderately progressive professional ideal and a strong identification with the planning profession. These results indicate a widespread phenomenon of conformorality within the planning profession, with planners frequently facing challenges when it comes to adhering to two sets of norms: the bureaucratic, and the professional. The study also discusses different mechanisms that contribute to the achievement and maintenance of planners’ conformorality, including compliance, identification, and internalisation.